Academic Diary Or Why Higher Education Still Matters - Back, Les (Goldsmiths Press, 2016)
Sharp and witty observations of academic life that range from the local to the global, from PowerPoint to the halls of power. Is a university education still relevant? What are the forces that threaten it? Should academics ever be allowed near Twitter? In Academic Diary, Les Back has chronicled three decades of his academic career, turning his sharp and often satirical eye to the everyday aspects of life on campus and the larger forces that are reshaping it. Presented as a collection of entries from a single academic year, the diary moves from the local to the global, from PowerPoint to the halls of power. With entries like "Ivory Towers" and "The Library Angel," these smart, humorous, and sometimes absurd campus tales not only demystify the opaque rituals of scholarship but also offer a personal perspective on the far-reaching issues of university life. Commenting on topics that range from the impact of commercialization and fee increases to measurement and auditing research, the diary offers a critical analysis of higher education today. At the same time, it is a passionate argument for the life of the mind, the importance of collaborative thinking, and the reasons that scholarship and writing are still vital for making sense of our troubled and divided world.